Integration of generalized B-spline functions on Catmull–Clark surfaces at singularities. (September 2016) - Wawrzinek, Anna; Polthier, Konrad
Abstract: Subdivision surfaces are a common tool in geometric modelling, especially in computer graphics and computer animation. Nowadays, this concept has become established in engineering too. The focus here is on quadrilateral control grids and generalized B-spline surfaces of Catmull–Clark subdivision type. In the classical theory, a subdivision surface is defined as the limit of the repetitive application of subdivision rules to the control grid. Based on Stam's idea, the labour-intensive process can be avoided by using a natural parameterization of the limit surface. However, the simplification is not free of defects. At singularities, the smoothness of the classically defined limit surface has been lost. This paper describes how to rescue the parameterization by using a subdivision basis function that is consistent with the classical definition, but is expensive to compute. Based on this, we introduce a characteristic subdivision finite element and use it to discretize integrals on subdivision surfaces. We show that in the integral representation the complicated parameterization reduces to a decisive factor. We compare the natural and the characteristic subdivision finite element approach solving PDEs on surfaces. As model problem we consider the mean curvature flow, whereby the computation is done on the step-by-step changing geometry. Highlights: A new subdivision finite element consistent with classical subdivision surfaces. Framework for solving PDEs on subdivision surfaces using the new approach. Solving the mean curvature flow on evolving Catmull–Clark subdivision surfaces. Comparison of our approach with the natural finite element approach.